2020
DOI: 10.1186/s43162-020-00025-w
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, clinical characteristics, and outcomes of acute pancreatitis in patients at Assiut University Hospital

Abstract: Background Acute pancreatitis is one of the main causes of acute abdomen. It may cause multi-organ failure or even death. High morbidity and mortality are associated with it. The research study aimed at evaluating the clinical characteristics and results of acute pancreatitis in our community. Results Mean age of patients was 50.96 ± 9.71 years and 30 (60%) patients were males. Gallstone was the most frequent etiology (56%) followed by idiopathic pancreatitis (26%). The majority of patients improved and only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…In this study, the incidence of gall stones was 71.1% whereas the incidence of alcohol induced pancreatitis was 26.6 % which is similar to Kashid et al [6], where the incidence of gall stones was found to be 36.4 % and that of alcohol 29.1 %,In the study done by Buchler MW et al [15], incidence of gall stones as 45 %. Other studies by Pezelli et al [13], Zarnescu et al [14] , Alkareemy EA et al [16] also shows that the incidence is more in biliary pathology.…”
Section: Discussionmentioning
confidence: 80%
“…In this study, the incidence of gall stones was 71.1% whereas the incidence of alcohol induced pancreatitis was 26.6 % which is similar to Kashid et al [6], where the incidence of gall stones was found to be 36.4 % and that of alcohol 29.1 %,In the study done by Buchler MW et al [15], incidence of gall stones as 45 %. Other studies by Pezelli et al [13], Zarnescu et al [14] , Alkareemy EA et al [16] also shows that the incidence is more in biliary pathology.…”
Section: Discussionmentioning
confidence: 80%
“…The only notable finding was the history of blunt abdominal trauma a day prior to the presentation of symptoms which was acquired through a thorough and detailed history. It is important to note that gallstones and alcohol abuse account for 70% of cases of acute pancreatitis [ 1 ]. Hypertriglyceridemia accounts for 2-5% and a large percentage of cases fall under the umbrella term idiopathic.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis resulting in pancreatic injury has multiple etiologies with gallstones and alcohol consumption contributing to a large majority of cases. Consequently, one uncommon cause of acute pancreatitis, direct abdominal trauma, often gets overlooked [ 1 ]. This case describes a 20-year-old male presenting to the hospital with isolated pancreatic tail injury after multiple blows to his abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the US has idiopathic acute pancreatitis at the top of the list, whilst in Latin America, acute biliary pancreatitis was the most frequent (11) . According to Alkareemy et al (12) , the most common etiology (56%) of acute pancreatitis patients were secondary to gall bladder stones, 26% were idiopathic, and 12% were ERCP. Idiopathic pancreatitis may be due to occult gall stones, dysfunction of the sphincter of Oddi, or cystic fibrosis in children or young adults (13) .…”
Section: Discussionmentioning
confidence: 99%